2011
DOI: 10.1002/hyp.8104
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of drought and the potential climatological driving factors in the Liao River basin

Abstract: Abstract:Spatiotemporal characteristics of drought based on the Standardized Precipitation Index (SPI) in the Liao River basin (LRB) are investigated in this study. High autocorrelation in SPI seems to lend itself to drought prediction. Drought is becoming more frequent, widespread, and severe in the LRB during the past several decades. Major factors affecting drought in this basin are analysed by investigating relationship between SPI and several circulations including western Pacific Subtropical High (WPSH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The SPI is an index based on the probability distribution of a long‐term precipitation time series (McKee et al ., , ). The calculation of SPI is presented as follows (Liu et al ., ): It is first fitted with an incomplete gamma probability density function to a given frequency distribution of precipitation at a station. pitalicθ=1baΓaitalicθa1eθ/b,θ>0where θ is the precipitation amount, a is the shape parameter, b is the scale parameter, and the gamma function is expressed as: Γa=0θa1eitalicθ…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The SPI is an index based on the probability distribution of a long‐term precipitation time series (McKee et al ., , ). The calculation of SPI is presented as follows (Liu et al ., ): It is first fitted with an incomplete gamma probability density function to a given frequency distribution of precipitation at a station. pitalicθ=1baΓaitalicθa1eθ/b,θ>0where θ is the precipitation amount, a is the shape parameter, b is the scale parameter, and the gamma function is expressed as: Γa=0θa1eitalicθ…”
Section: Methodsmentioning
confidence: 97%
“…The maximum likelihood method is used to estimate the optimal values of a and b (Liu et al ., ). {a=14Atrue(1+1+4A3true)b=italicθtrue¯aA=normalIntrue(trueθ¯true)Initalicθnwhere n is the number of precipitation records.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The SPI is easy to apply, and has various advantages, as discussed by Hayes et al (1999). Therefore, the SPI has been widely used to investigate meteorological droughts in many countries, including Australia (Wen et al 2011), Canada (Quiring and Papakryiakou 2003), China (Wu et al 2001;Liu et al 2012), Greece (Tsakiris and Vangelis 2004;Dimitrakopoulos et al 2011), India (Mishra and Desai 2005), Italy (Bonaccorso et al 2003;Piccarreta et al 2004), Spain (Lana et al 2001;Pasho et al 2011), Taiwan (Shiau 2006;Chen et al 2009), and the United States (Edwards and McKee 1997;Ji and Peters 2003).…”
Section: Introductionmentioning
confidence: 99%
“…circulation effects on precipitation may have similar effects on drought [29]. Previous studies indicated that weaker East Asian Summer Monsoon (EASM) was the main cause responsible for decreasing northward propagation of water vapor flux, causing different wet (dry) tendency in South (North) China [30].…”
mentioning
confidence: 99%